Robust Stability of Dynamical System - Ossowski, A. (Engineering Transactions, 1996)
A general concept of the robust stability of uncertain nonlinear dynamical systems is given. By using the method of optimal Lyapunov functions, the robust stability analysis is performed in the general case of a multidimensional system described by ordinary differential equations. The presented approach is applied to the problem of stability of affine systems with nonstationary structural disturbances. An illustrative example of a perturbed oscillator is given.